Do Additional Cardiac Surgical Procedures Increase the Surgical Risk in Patients 80 Years of age or Older Undergoing Coronary Bypass Gragting - Korhan Erkanlı; Timuçin Aksu; Ünal Aydın; Onur Şen; Erhan Kutluk; Mehmet Kaya; Mehmet Yeniterzi; İhsan Bakır (Haseki Tıp Bülteni, 2014)
Aim: In association with increasing life expectancy, the number of elderly individuals undergoing coronary bypass grafting (CABG) and additional cardiac surgical procedures are increasing. In this study, we evaluated the effects of additional cardiac procedures and preoperative risk factors for postoperative mortality and morbidity in patients 80 years of age and older. Methods: The records of 29 patients aged 80 years and older (82.86±2.91) who had undergone coronary bypass surgery in the department of cardiac surgery between September 2009 and June 2012, were retrospectively reviewed. The subjects were divided into two groups: group 1 included the patients who had undergone CABG, group 2 consisted of those who had undergone CABG and additional cardiac procedures. Results: The mean age of the patients [14 male (48.3%) 15 female (51.7%)] was 82.86±2.91 years. The left internal thoracic artery was harvested for all patients. The mean number of graft per patient was 3.07±0.95. Carotid endarterectomy was performed in 3 patients before CABG. CABG and aortic valve replacement were performed in 1 patient. CABG, mitral valve replacement ant tricuspid plasty were performed in another patient. Furthermore, in one patient, abdominal aortic graft replacement due to ruptured abdominal aortic aneurysm and CABG was performed at the same session. The mean EuroSCORE was 5.06±5.16. Postoperative 30 days mortality was 6.8%, and the mean length of stay in hospital was 10.45±8.18 days. Conclusion: Coronary bypass surgery is an acceptable treatment method in patients 80 years of age and older. Although additional cardiac procedures may increase sugical risks, they can be successfully performed. (The Medical Bulletin of Haseki 2014; 52: 14-8)